COST EFFECTIVENESS AND EFFICIENCY ANALYSIS OF HOSPITAL WASTEWATER TREATMENT PLANT: A SYSTEMATIC REVIEW - Nainggolan, Catherine Maname Uli; Permanasari, Vetty Yulianty (Proceedings of the International Conference on Applied Science and Health, 2017)
Backgrounds: Hospital waste management had become an international attention. One of the first meeting by Solid Hazardous Waste was related to domestic waste and medical waste. The previous study showed that nationally hospital solid waste expectedly reach 376.089 ton per day and the volume of wastewater was 48.985,70 ton per day. Aims: The purpose of this study is to examine the literatures on analysis of the cost effectiveness and efficiency hospital Wastewater Treatment Plant. Methods: This systematic review was based on Protocol Prisma. Literature searches were conducted using the electronic databases Google Scholar (2011 to present), SpringerLink, and Proquest.Over a total of 3.834 potential articles, 9 met all inclusion criteria. Results: Cost problems were founded due to there was no good financial planning, maintenance costs, and the wastewater quality supervision. The budget of wastewater treatment only focuses to the cost of damage, but only enough for one time laboratory examination. Moreover, we also highlighted another factors affected to effectiveness and efficiency where there was no regular training for sanitarian, and as the results, sanitarian cannot determine the best effective method, finally the budgets were only for authoritarian system. This paper also reviews methods and applications to reduce the cost in electrical, chemical, and maintenance, by new wastewater treatment alternatives. If compared the two techniques, extended aeration and sequencing batch reactors, evidently, sequencing batch reactor had lower cost than extended aeration. Conclusions: The cost effectiveness and efficiency of wastewater management can be achieved by good management systems, good knowledge about waste, and different methods result different efficiency too.Â